Use of Precision Dairy Farming Technologies in Improving Dairy Cattle Welfare (Indian Journal of Animal Production and Management, 2024)
Precision Dairy Farming (PDF) is a new  emerging field of sensor technology with the related  algorithms, interfaces, and wide applications that  defines modern cattle farming. This paper gives an  insight into the presently available technologies that  can be implemented in farms of various sizes  whereby a large unit of animals can be still be  observed with individual attention. There are a large  number of technologies with varying levels of  applications. Hence this paper classifies these  technologies from the perspective of Livestock  Production and Management into four pillars viz.,  breeding, feeding, weeding and heeding. Each of  these pillars is explained with the latest available  information as applicable to Indian conditions.  Nevertheless, countless entrepreneurs have  already adopted these technologies. This is just an  attempt to update the readers about the latest  developments in this field and the potential  application at dairy farms for improved milk  production.
Keywords: precision dairy farming; dairy cattle welfare